2022
DOI: 10.7717/peerj.12654
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analyses of C2H2 zinc finger transcription factors in Pleurotus ostreatus

Abstract: The C2H2-type zinc finger proteins (C2H2-ZFPs) regulate various developmental processes and abiotic stress responses in eukaryotes. Yet, a comprehensive analysis of these transcription factors which could be used to find candidate genes related to the control the development and abiotic stress tolerance has not been performed in Pleurotus ostreatus. To fill this knowledge gap, 18 C2H2-ZFs were identified in the P. ostreatus genome. Phylogenetic analysis indicated that these proteins have dissimilar amino acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Previous reports indicate that they play an important role in cucumber, Arabidopsis , wheat, and tomato [ 39 , 40 , 41 , 42 ]. Therefore, many researchers have tried to perform genome-wide analysis on C2H2-ZFP s in various species, such as tomato, wheat, grape, and oyster mushroom [ 43 , 44 , 45 , 46 ], but little is known about sorghum C2H2-ZFP proteins. In this study, we carried out a genome-wide study of the S. bicolor C2H2-ZFP family and identified a total of 145 SbC2H2-ZFP members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports indicate that they play an important role in cucumber, Arabidopsis , wheat, and tomato [ 39 , 40 , 41 , 42 ]. Therefore, many researchers have tried to perform genome-wide analysis on C2H2-ZFP s in various species, such as tomato, wheat, grape, and oyster mushroom [ 43 , 44 , 45 , 46 ], but little is known about sorghum C2H2-ZFP proteins. In this study, we carried out a genome-wide study of the S. bicolor C2H2-ZFP family and identified a total of 145 SbC2H2-ZFP members.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of a gene is often used to predict its function. Previous findings have shown that the expression of C2H2-ZFP genes was affected by tissue differences and various abiotic stresses [ 46 , 53 ]. Our results showed that among the selected SbC2H2-ZFPs, most genes were expressed in roots higher than those in leaves or stems, but almost all SbC2H2-ZFP members were expressed in roots, stems, and leaves.…”
Section: Discussionmentioning
confidence: 99%
“…No such changes were observed for most other enzymes [ 29 ]. The expression of genes coding for zinc finger proteins in P. ostreatus was regulated by developmental processes, phytoeffectors and abiotic stress [ 30 ], whereas, in line with a genetic study [ 13 ], the spectrum of lectins changed from mycelium to primordium to mature fruiting body [ 31 ]. A lentinan degrading β -1,3-glucanase of L. edodes occurred after the harvest of fruiting bodies but was not detectable in mycelia and young fruiting bodies [ 32 ].…”
Section: From Genomics To Proteomics: Proteins Enzymes and Amino Acidsmentioning
confidence: 99%
“…They thrive on most of the substrates shown in Table 1 by quickly inducing large enzymatic networks (own experiments, data not shown). As a result, the composition of the fruiting bodies depends on the growth substrate [ 33 , 55 , 57 , 60 , 67 , 72 , 74 ], the strain chosen [ 33 , 60 , 74 , 75 , 76 , 77 , 78 , 80 ], its developmental stage [ 29 , 30 , 31 , 32 , 38 ], and the associated adverse or beneficial microbial community [ 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ] and is thus variable like no other food. The same applies to the mass production of fungal mycelia.…”
Section: Differences Between Fermenter Produced Fungal Mycelia and Fr...mentioning
confidence: 99%
“…Due to the extensive interest in their positions in the physiological regulation of resistance, some ZFP families have been identified and investigated in various plants, such as A. thaliana , Solanum tuberosum , Pleurotus ostreatus, and Cucumis sativus [ 18 , 19 , 20 , 21 , 22 ]. However, this functionally diverse family of proteins has not been studied in wheat ( Triticum aestivum ).…”
Section: Introductionmentioning
confidence: 99%